The "Pharsalia" of Lucan in the thought of Saint Augustine - Sarr, Pierre (Gerión. Revista de Historia Antigua, 2012)
When Alaric invaded Rome, this event was considered as a considerable disillusion for the Romans. Emperors were thus considered as responsible for this catastrophy, as they had abandoned the antic religion for Christianism. They were however comforted in this great disillusion when they saw the corpses of the dead Christians, abandoned on the ground without being buried. They saw it as being gods’ revenge. Relying on pagan authors -especially on Lucain- Augustin demonstrates the responsibility of Rome in the conflicts which divide people, but also the inefficacy of pagan gods. Moreover, he demonstrates that the lack of burial-place can not be a proof of eternal condamnation.